Development of a compact dynamometer to evaluate propulsive power on the wheelchair - Oliveira, S. F.; Oliveira, L. S.; Bione, A. G.; Silva, C. L.; Costa, M. C. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
The methods and instruments used to determinate kinetic parameters about the manual wheelchair propulsion, as well as power output (PO), have disregarded interactions related to wheelchair-user system (subject and wheelchair), besides their excessive size and complex utilization. Therefore, the aim of this study was to developed of a new dynamometer to evaluate PO on the wheelchair, and determine the specificity of the electromechanical system. The mechanical portion of the prototype consists of three parallel cylindrical rollers mounted on rotating axes (Easy Scroll, Brazil). In the central roller are attached rotation sensors. Between the two kits connects a calibration system to calculate the dynamic moment of inertia. The PO was determined by measurement of the inertia and rotations (RPM) of cylinders. Data about RPM are acquired by magnetic sensors connected to Arduino board converter (Sparkfun, USA) and this linked to a computer. The converter is programmed to read the signs at each rotation for own algorithms providing two software environments: the first for calibration system and the second to determinate the PO. The data are sent to a computer and converted in graphics (PO versus RPM) by PLX-DAQ (Parallax, USA) and Microsoft Excel 2007. This study was approved by the ethics committee of the University of Pernambuco (Recife/PE/Brazil). Non-wheelchair users (men, 21±2 years, n=5) were tested on the same basketball wheelchair in four different styles of propulsion selected and randomized in advance: pumping, single-looping, double-loop and semicircular. The subjects were instructed to keep pace and thrust comfortable at all time. Independent investigators counted the number of propulsions executed by the subject to determine the freely chosen cycle frequency (FCF: 100%) to each volunteer at the end of last minute familiarization. The resting heart rate was measured in the seated position after 10 minutes of rest. The experimental protocol for each style consisted of a continuous effort of 5 minutes at 120% FCF. Push frequency was controlled by audio metronome (M&M Systems, Germany). Overall and local (active muscles) rating perceived exertion and heart rate (Polar FS1, Finland) were collected at the end of each minute. Subjects started the following style after heart rate recovery at baseline. The selected variables were analyzed using the Kruskal-Wallis and the level of significance set at p<0.05. There were no significant differences in the heart rate and overall and specific rating perceived exertion (Figure 2, p>0.05). This result suggests one basic characteristic of dynamometry and a new possibility to evaluate performance on the wheelchairs in opposition to methods of measuring the amount of work done.